Impact of Heartfulness Meditation on Perceived Stress and Mental Well-being - Jyothi, P K; Sudhikumar, K B; Sreeraj, S K (International Research Journal of Ayurveda & Yoga, 2023)
The prevalence of mental illness and the impact of stress have become increasingly concerning in the context of our rapidly evolving society. As a result of the aforementioned factors, both mental and physical health are impacted, leading to the emergence of numerous lifestyle diseases eventually. To effectively address the stress experienced at the community level, the implementation of meditation has been empirically demonstrated to be an efficacious strategy for managing and adapting to various challenging circumstances. In Ayurveda classics, Swasthavritta (regimen for healthy lifestyle) various Acharyas are mentioned in detail to become a healthy individual in which Dhyana (Meditation) is essential for both psychological and physical well-being. School of Fundamental Research in Ayurveda under Kerala University of Health Sciences conducted a daily meditation session for registered participants of 30-min duration, guided by preceptors from heartfulness organization which continued for 90 days. Heartfulness meditation is a form of meditation that focuses on the heart as its central point of practice. By cultivating a sense of inner calmness, this practice aims to alleviate stress and promote overall well-being. This comprised guidelines and information regarding heartfulness relaxation, meditation, cleaning, and connecting with the source before going to bed. Among the entire group of 20 participants, only 12 individuals successfully completed the entirety of the 90- day duration. A subjective evaluation was conducted on a sample of 12 participants using a self-assessment survey that included the Perceived Stress Scale (PSS) and the WHO (Five) Well-being Score. This evaluation was given both before and after the study. A statistical analysis was conducted using the PSS and the WHO (Five) well-being questionnaire. The obtained P-value was found to be <0.05, indicating a high level of significance. This suggests that the meditation program conducted was effective in reducing stress and promoting the well-being of the participants.